52/100
26/50
13/25
These will all do.
Answer:
x - 6 = 24
Step-by-step explanation:
1/3 x - 2 = 8
Multiply all the terms by 3
3*1/3x - 2*3 = 8*3
x - 6 = 24
14.86 is the answer to this question
Answer:
-5
Step-by-step explanation:
The answer is -5 because we have -2 as x. The function is h(x)=3x+1. 3 times -2=-6. When we add 1 to the result, we have -5 as the answer. Hope it helps!
Answer:
The total value of the given expression is 12.
Step-by-step explanation:
(-2 + 1)² + 5(12 ÷ 3) - 9
First, do the expressions within the parentheses.
(-1)² + 5(4) - 9
Next, simplify the exponents.
1 + 5(4) - 9
Next, multiply 5 by 4.
1 + 20 - 9
Add 1 and 20 together.
21 - 9
Subtract 9 from 21.
12
So, the final answer to this equation is 12.